Evaluation of Occupational Health and Safety (OHS) Based on HIRARC Method to Improve Workers' Performance on Exploration Well Drilling Project at PT.X: Evaluasi Kesehatan dan Keselamatan Kerja (K3) Berbasis Metode HIRARC untuk Meningkatkan Kinerja Para Pekerja pada Proyek Pengeboran Sumur Eksplorasi di PT.X - Said, Nandiva Aurellia Putri; Yasinta, Rezi Berliana; Chaesa, Adinda; Mulya, Mifthah Alvito; Nuresa, Keny Islam; Rizaldi, Teuku Rizky Ananda (Universitas Negeri Surabaya, 2025)
This study aims to analyze and evaluate the application of Occupational Health and Safety (OHS) using the HIRARC (Hazard Identification, Risk Assessment and Risk Control) approach to improve the performance of workers in the environment of PT X's TTN-001 exploration well drilling project. The research method used is a descriptive quantitative approach through distributing questionnaires, field observations, interviews, and document analysis. A total of 80 respondents from the field workforce became the research sample. The results showed that the highest potential hazards came from work activities at heights, welding without eye protection, and high noise exposure. Risks were assessed using a risk matrix based on likelihood and impact levels. Risk control is carried out based on the control hierarchy which includes elimination, substitution, engineering, administrative, and the use of PPE as a last resort. The evaluation showed that although PPE had been provided, compliance with its use was still low. Recommendations were given in the form of strengthening training, periodic HSE audits, increased supervision and procurement of more ergonomic PPE.